Convolutional Neural Network-based Object Detection (International Journal of Innovative Research in Computer Science & Technology, 2022)
In the midst of the efforts in an item identification, region CNNs (rCNN) stands out as the most  impressive, combining discriminatory exploration, CNNs,  sustenance vector machines (SVM), and bounding box  regression to achieve excellent object detection  performance. We propose a new method for identifying  numerous items from pictures using convolution neural  nets (CNNs) in this presented study. The authors of the  presented study use the edge box technique to create region  suggestions from edge maps for each picture in our model,  and then forward pass all of the proposals through a well accepted CaffeNet prototype. Then we extract the yield of  softmax that generally is most recent layer of CNN, to  determine CNNs score for every proposal. One of the  greedy suppression methodology referred to as non maximum suppression (NMS) method is then used to  combine the suggestions for each class separately. Finally,  we assess each class's mean average precision (mAP). On  the PASCAL 2007 test dataset, our model has a mAP of  37.38 percent. In this work, we also explore ways to  enhance performance based on our model.
Keywords: Convolutional Neural Network; Datasets; Object discovery; Region proposal; Regression